2021
DOI: 10.1287/mnsc.2020.3585
|View full text |Cite
|
Sign up to set email alerts
|

A Test Score-Based Approach to Stochastic Submodular Optimization

Abstract: We study the canonical problem of maximizing a stochastic submodular function subject to a cardinality constraint, where the goal is to select a subset from a ground set of items with uncertain individual performances to maximize their expected group value. Although near-optimal algorithms have been proposed for this problem, practical concerns regarding scalability, compatibility with distributed implementation, and expensive oracle queries persist in large-scale applications. Motivated by online platforms th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 57 publications
2
7
0
Order By: Relevance
“…We also give a more refined analysis for the regime of regular item costs by parametrizing variations in item costs. As a byproduct of our analysis, we recover the result of Sekar et al (2020) for the cardinality constrained case. We further derive approximation guarantees for the sub-classes of value functions with bounded curvature, for the notion of curvature originally defined by Conforti and Cornuéjols (1984) initially for set functions.…”
Section: Our Contributionssupporting
confidence: 56%
See 4 more Smart Citations
“…We also give a more refined analysis for the regime of regular item costs by parametrizing variations in item costs. As a byproduct of our analysis, we recover the result of Sekar et al (2020) for the cardinality constrained case. We further derive approximation guarantees for the sub-classes of value functions with bounded curvature, for the notion of curvature originally defined by Conforti and Cornuéjols (1984) initially for set functions.…”
Section: Our Contributionssupporting
confidence: 56%
“…Kleinberg and Raghu (2015) used the test scores for the problem of constructing a team whose best r players have high performance (we will discuss this further in Section 2.2). Sekar et al (2020) showed that the greedy algorithm based on the replication test score achieves a constant approximation for the cardinality constrained submodular maximization if the objective satisfies the extended diminishing returns property. They also showed that using the mean or quantile value as a score metric does not guarantee a constant approximation for a function with the property (the CES function, defined in Section 2.2).…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations